Kinetic analysis of the support leg in soccer instep kicking - Inoue, K.; Nunome, H.; Sterzing, T.; Shinkai, H.; Ikegami, Y (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of the present study was to illustrate the kinetic aspect of the support leg during soccer instep kicking. The motion was captured together with the ground reaction force using a motion capture system. Moments and angular velocities of ankle, knee and hip joint for the support leg were calculated. The ankle joint was passively rotated threedimensionally, during which these motions were counteracted to the joint moments. The knee joint motion, likewise, counteracted to the joint moment from the instant of the touch-down to just before ball impact. It is likely that the ankle and knee joints have a role in attenuating the impact of landing. In contrast, positive power due to the knee and hip extension moments appeared just before ball impact. It can be assumed that those motions may serve to lift the body thereby indirectly contributing the kick leg swing.